Ascorbic acid-mediated zero-valent iron enhanced hydrogen production potential of bean dregs and corn stover by photo fermentation. (April 2023) - Zhu, Shengnan; Zhang, Yang; Zhang, Zhiping; Ai, Fuke; Zhang, Huan; Li, Yameng; Wang, Yaozhe; Zhang, Quanguo
Graphical abstract: Highlights: The best dosage of ascorbic acid to mediate 400 mg/L Fe(0) was 150 mg/L. Ascorbic acid promoted the Fe(Ⅱ) generation through reduction and chelation. H2 produced from ascorbic acid-Fe(0) was 2.7–27.5% higher than Fe(0) at pH 6–9. Initial pH had an important effect on H2 production and Fe(0) reactivity. Abstract: Ascorbic acid was introduced to enhance the performance of zero-valent iron (Fe(0)) in hydrogen production by photo fermentation of bean dregs and corn stover. The highest hydrogen production of 664.0 ± 5.3 mL and hydrogen production rate of 34.6 ± 0.1 mL/h was achieved at 150 mg/L ascorbic acid, which was 10.1% and 11.5% higher than that of 400 mg/L Fe(0) alone. The supplement of ascorbic acid to Fe(0) system accelerated the formation of Fe(Ⅱ) in solution due to its reducing and chelating ability. Hydrogen production of Fe(0) and ascorbic acid-Fe(0) (AA-Fe(0)) systems at different initial pH (5, 6, 7, 8 and 9) was studied. Result showed that hydrogen produced from AA-Fe(0) system was improved by 2.7–27.5% compared with Fe(0) system. The maximum hydrogen production of 767.5 ± 2.8 mL was achieved with initial pH 9 in the AA-Fe(0) system. This study provided a strategy for enhancing biohydrogen production.